Efeitos do cobre em aspergillus niger ucp/wfcc 1261 : aspectos morfológicos, ultraestruturais e bioquímicos - Luna, Marcos Antônio Cavalcanti (2014)
The knowledgement about the biodiversity and the bioprospection of new microorganisms are the main focus of the biotechnological age, since the use of these organisms in the areas of food, health, environment and industry is increasing in the current world-wide scene. The use of microorganisms is one alternative potential for ambient and industrial biotechnology. Present proposal aims at to provide informations about the physiological mechanisms by using the evaluation of growth, accumulation of polyphosphate, total proteins, extracellular enzyme activity, antioxidant enzyme systems and metal renoção by Aspergillus niger UCP / WFCC 1261, isolated from caatinga, depending on the induction of oxidative stress by copper in the culture medium. The isolate was grown on Sabouraud medium containing copper at concentrations of 0.5 mM, 1 mM and 2 mM for 15 days under a temperature of 28 ° C. The variation of polyphosphate, total protein and antioxidant enzyme activities were measured as a function of cultivation in different media in the presence and absence of metal. For the determination of enzyme activities, extracellular specific methodologies were used during growth in the absence and presence of the metal ion. Morphological and ultrastructural aspects were analyzed by light microscopy and scanning electron microscopy. The results could be used to generate essential knowledge related to the behavior understanding face the copper presence and its potential application in the biotechnological processes related to environment remediation polluted with the heavy metal.